Stock Market Returns and Consumption - Marco Di Maggio; Amir Kermani; Kaveh Majlesi (Institute of Labor Economics (IZA), 2018)
This paper employs Swedish data on households' stock holdings to investigate how consumption responds to changes in stock market returns. We instrument the actual capital gains and dividend payments with past portfolio weights. Unrealized capital gains lead to a marginal propensity to consume (MPC) of 13 percent for the bottom 50% of the wealth distribution, but a flat 5 percent for the rest of the distribution. Households' consumption is significantly more responsive to dividend payouts across all parts of the wealth distribution. Our findings are consistent with households treating capital gains and dividends as separate sources of income.
Keywords: E21; D15; G12; 330; capital gain; dividend income; consumption; near-rational behavior